Phytotherapy: The Significance and Application of Selected Medicinal Plants in Modern Medicine - Dominiczak, Kinga; Kopaczyńska, Adrianna; Szafrańska, Katarzyna; Janiak, Aleksandra; Niemirka, Szymon; Grądalski, Łukasz; Dębicki, Filip (Quality in Sport, 2025)
Introduction: Phytotherapy, the field focused on utilizing medicinal plants for the prevention and treatment of diseases, plays a crucial role in a sustainable approach to healthcare. In the context of growing interest in natural therapies, attention is increasingly directed toward species such as Urtica dioica (common nettle), Berberis vulgaris (common barberry), and Withania somnifera (common ashwagandha). These plants, renowned for their richness in active compounds like flavonoids, alkaloids, lignans, and withanolides, offer a wide range of therapeutic effects. This paper examines the role of these species in modern medicine, highlighting their importance in the treatment and prevention of chronic conditions such as diabetes, cardiovascular disorders, and cancer. It discusses their unique biochemical properties, mechanisms of action, and evidence of efficacy gathered through clinical studies. With advanced extraction techniques and phytochemical analysis, the pharmacological potential of these plants has been thoroughly explored, opening up new possibilities for integrating natural ingredients into holistic healthcare approaches. Phytotherapy based on these plants reflects not only their centuries-old tradition but also their growing importance in contemporary, sustainable medicine. Aim of study: The aim of this scientific paper is to summarize the available knowledge on the significance and application of various medicinal plants used in modern medicine. Particular emphasis has been placed on their impact on metabolic syndrome, obesity, as well as the gastrointestinal, cardiovascular, and renal systems. Material and methods: The literature available in PubMed, and the Google Scholar database was reviewed using the following keywords: , phytotherapy’’; , herbal therapy’’; , botanical characteristics”; , medicinal plants”; , utrica dioica”; , berberine”; , barberis vulgaris”; “withania somnifera”